Problems of criminal liability of legal entities - Malanchuk, Petro (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The doctrinal provisions of the criminal law of Ukraine are analyzed. The issue of non-compliance with international standards in the field of criminal law and traditional approaches to the main institutions of criminal law of Ukraine is considered. The article discusses the theoretical and practical application of criminal liability in relation to legal entities, taking into account the experience of criminal law. Ways are proposed to improve national criminal legislation, taking into account foreign experience. The problem of criminal liability of legal entities to this day remains debatable. The question of the appropriateness of introducing such responsibility became relevant after the adoption by the Verkhovna Rada of Ukraine of the Law of Ukraine of May 23, 2013 “On Amending Certain Legislative Acts of Ukraine Concerning the Implementation of the Action Plan for the Liberalization of the European Union Visa Regime for Ukraine Regarding the Liability of Legal Entities”. In particular, the provisions of this law provide for the application of criminal measures to legal entities. Measures of criminal nature can be applied to subjects privately and public law, residents and non-residents; Dents of Ukraine, including enterprises, establishments new or organizations, government bodies, bodies the authorities of the ARC, local governments, organizations certified by them in the appropriate orderfunds, international organizations and others legal entities created in accordance with the requirements of national or international law. As a rule, legal entities apply-material measures are taken and all problems can be solved (and they are solved) in within other areas of law. For legal a special system of penalties was created which, in essence, they are not criminal penalties. That is why under the Criminal Code of Ukraine to legal entities criminal law measures are applied character: fine, confiscation of property, liquidation.Therefore, to ensure that the relevant rules are effective The Criminal Code of Ukraine should be studied internationally experience and its implementation in the national criminal legislation.